2022
DOI: 10.1055/s-0042-1757904
|View full text |Cite
|
Sign up to set email alerts
|

Permanent First Mandibular Molar: Loss Prevalence and Pattern among Saudis in Al-Ahsa

Abstract: Objectives The permanent first mandibular molar (PFMM) is the first tooth to erupt, usually at the age of 6 years. It is the most effective oral masticatory unit due to its wide occlusal surface and its role in favorable occlusion. This study describes the prevalence of PFMM loss and the reasons for extraction in a group of King Faisal Dental Complex Clinics (KFUDC) Saudi attendees. In addition, to report postextraction complications, consider the gender, age, and the time elapsed from the moment of the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recent epidemiological studies exhibited that 60-90% carious lesions occurred in the pits and fissures of permanent first molars, despite the preventive ongoing programs [15]. More than 50% children over 11 years age had been reported for caries in the permanent first molars [7]. The preferred therapy in severely compromised permanent first molar with poor prognosis might be extraction, although being non-restorable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent epidemiological studies exhibited that 60-90% carious lesions occurred in the pits and fissures of permanent first molars, despite the preventive ongoing programs [15]. More than 50% children over 11 years age had been reported for caries in the permanent first molars [7]. The preferred therapy in severely compromised permanent first molar with poor prognosis might be extraction, although being non-restorable.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective extraction time is the childhood as suggested by previous studies, however with limited scientific evidence [2,7,8]. Eichenberger et al [9] finds better clinical outcomes after P1Ms extraction in younger children (8-11.5 years) compared to older age [10].…”
Section: Introductionmentioning
confidence: 99%
“…Our study was focused on adults (>18 years old). To the best of our knowledge, no studies primarily focused on adult populations except for a recent clinical study [ 5 ]. However, their study focused on mandibular first permanent molars only.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, first permanent molars are the highest susceptible teeth to caries due to their early eruption [ 3 ]. Caries was found to be the main reason for permanent tooth extraction [ 4 , 5 ]. Previous studies in Saudi Arabia have found an 83% prevalence of caries among children, and the prevalence of missing FPMs was higher with mandibular FPMs than the maxillary FPMs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding agrees with past studies conducted in Saudi Arabia. 39 , 40 Caries and periodontal disease are mostly avoidable causes of tooth loss if detected early during routine dental visits. However, first-time and previous attendees visited dental clinics at a late stage of the disease that required teeth extraction either due to the high cost of the treatment or because there was no other treatment option left.…”
Section: Discussionmentioning
confidence: 99%